New Directions in Auditing Education. - Carmichael, D. R.; Willingham, John J. (The Accounting Review, 1969)
The best available indication of the present state of college level auditing education can be deduced by considering widely used textbooks. A recent survey of textbooks used by members of the American Association of Collegiate Schools of Business revealed that the five leading textbooks are used in over eighty-seven percent of, the schools. In all of these books predominant emphasis is placed on verification of financial statement categories and a majority of the chapters are directed to serial treatment of specific general ledger accounts. Within these chapters a great deal of detailed procedural advice is given. There are certain current trends in accounting education, in addition to a preference for conceptual material, that must be considered in shaping the content of the auditing course. There is not room enough for remedial courses in the present accounting curriculum. The auditing course should not be used as a review of accounting theory, which should have been learned in intermediate accounting, and there is not time to cover many features of internal control, which are more appropriately covered in the systems course.